Amblyomma cajennense is an intrastadial biological vector of Theileria equi - Scoles, Glen A; Ueti, Massaro W (Parasites & vectors, 2013)
BACKGROUND: The apicomplexan hemoprotozoan parasite Theileria equi is one of the etiologic agents causing equine piroplasmosis, a disease of equines that is endemic throughout large parts of the world. Before 2009 the United States had been considered to be free of this parasite. Occasional cases had occurred but there was no evidence for endemic vector-borne transmission in the U.S. until a 2009 outbreak in Texas in which Dermacentor variabilis and Amblyomma cajennense were implicated as vectors. Although D. variabilis has previously been shown to be a competent laboratory vector, studies suggested A. cajennense was not a competent transstadial vector, even though the presence of this tick species on horses in South American is epidemiologicaly correlated with higher a prevalence of infection. In this study we tested the transstadial and intrastadial vector competence of D. variabilis and A. cajennense for T. equi. METHODS: A tick passaged T. equi strain from the Texas outbreak and ticks colonized from engorged females collected off horses on the outbreak ranch in Texas were used for these studies. Nymph or adult ticks were fed on infected horses and transmission fed on naïve horses. Infections were tracked with PCR and serology, dissected tick tissues were tested with PCR. RESULTS: A. cajennense transmitted T. equi intrastadially when adult ticks acquired infection by feeding on an infected horse, and transmitted to a naïve host on subsequent reattachment and feeding. D. variabilis failed to transmit in the same experiment. Transstadial transmission was not successful for either tick species. PCR on DNA isolated from eggs of females that had fed on an infected horse suggests that there is no transovarial passage of this parasite by either tick species. CONCLUSION: This work confirms that ticks from the Texas population of A. cajennense are competent intrastadial vectors of T. equi. We propose that the most likely natural mode of transmission for this parasite/vector combination in the Texas outbreak would have been biological transmission resulting from adult male ticks moving between infected and uninfected horses. The intrastadial mode of transmission should be considered as one equally possible scenario whenever implicating vectors of T. equi.